Pumpkin circle : the story of a garden - Levenson, George; Thaler, Shmuel (Berkeley, Calif. : Tricycle Press, 1999)
Rhyming text and photographs follow a pumpkin patch as it grows and changes, from seeds to plants to pumpkins ready to harvest, to jack-o-lanterns and then to seeds again.
Keywords: Pumpkin -- Juvenile literature; Pumpkin -- Life cycles -- Juvenile literature; Pumpkin